A Comprehensive Systematic Review of The Effect of Topical Corticosteroid and Vitamin D Analog Combination Therapy on Psoriasis Remission Duration - Dio Vaszdly Pramana Sukardi; Finda Rahmanisa (The International Journal of Medical Science and Health Research, 2025)
Introduction: Topical therapy remains a cornerstone for mild-to-moderate psoriasis, but relapse after treatment cessation is a major challenge. The combination of topical corticosteroids (TCS) and vitamin D analogs (VDAs) has demonstrated superior efficacy over monotherapies for active treatment, yet comprehensive evidence on its long-term impact on remission duration is needed. Methods: A systematic review was conducted based on a structured screening of literature from databases, adhering to predefined criteria. Studies involving adult patients with cutaneous psoriasis, evaluating concurrent topical TCS/VDA combination therapy, reporting remission duration or relapse data with ≥4 weeks follow-up, and employing controlled designs were included. Data on treatment regimens, remission definitions, relapse times, safety, and patient characteristics were extracted from 40 eligible sources. Results: Proactive, long-term management with co-formulated calcipotriol/betamethasone dipropionate (Cal/BD) foam was the most effective strategy. The pivotal PSO-LONG trial demonstrated that twice-weekly proactive application nearly doubled the median time to first relapse (56 vs. 30 days) compared to reactive management, resulting in 41 additional days in remission per year (Lebwohl et al., 2020). Similar benefits were observed for other combinations, such as halobetasol/tazarotene lotion, which maintained treatment success in 38.2% of patients 4 weeks post-cessation versus 21.0% with halobetasol alone (Pariser et al., 2018). Systematic reviews confirmed the combination's superiority over VDA monotherapy (RR 2.28 for clearance) and a modest but significant benefit over potent corticosteroid monotherapy (RR 1.22) (Samarasekera et al., 2013; Queirós et al., 2017). The therapy was well-tolerated long-term, with no significant safety concerns over 52 weeks. Discussion: The combination's efficacy stems from complementary anti-inflammatory, immunosuppressive, and keratinocyte-normalizing effects. The proactive regimen's success highlights the importance of treating subclinical inflammation to prevent relapse. Heterogeneity in outcomes is explained by differences in protocols (proactive vs. reactive), formulations (foam superiority), baseline disease severity, and combination types (co-formulated vs. sequential). The therapy offers a favorable risk-benefit profile, reducing overall corticosteroid exposure through sustained remission. Conclusion: Proactive, long-term maintenance therapy with topical corticosteroid and vitamin D analog combinations, particularly Cal/BD foam, significantly prolongs psoriasis remission, reduces relapse frequency, and is a safe and effective first-line strategy for long-term disease control.